Rancang Bangun Model Diseminasi Informasi Pada Destinasi Pariwisata Budaya Situs Bojong Galuh Karangkamulyan Kabupaten Ciamis - Winoto, Yunus; Nur'Fadilla, Firda Ainadya (Jurnal Ilmiah Pariwisata, 2022)
The purpose of this study was to design a model for information dissemination in the tourism destination area of ​​the Bojong Galuh Karangkamulyan site in the form of leaflets and booklets. The approach used in this information dissemination model uses a communication approach by applying the elements of communication which include aspects of the communicator, message, context, media, and recipient. The method used in this study uses action research which was carried out in two research cycles, each cycle consisting of several stages, namely planning, action, observation, and reflection stages. Results Based on research by looking at several indicators of success before and before this research was conducted, it was revealed that one of the factors was the lack of recognition of the Situ Bojong Galuh Karangkamulyan tourism area, this was still a lack of promotion. In an effort to overcome this, researchers designed an information dissemination model, as well as complete information and easy access to information. Improvements in the design and content of messages in leaflets and the provision of special booklets for the Bojong Galuh Karangkamulyan Site which can also be accessed online, so that through promotional media the wider community can know and be interested in getting to know the tourist area of ​​the Bojong Galuh Karangkamulyan Site. Keywords: Information Dissemination, Tourism Destinations, Cultural Tourism, Promotion, Site Tourism